2015
DOI: 10.1039/c5ra04335b
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and organ-specific toxicity of cucurbit[7]uril: in vivo study on zebrafish models

Abstract: The macrocyclic molecular container cucurbit [7]uril (CB[7]), the most water-soluble homologue in the cucurbit[n]uril family (n = 5-8, 10, 14), has been evaluated for its in vivo toxicity profile, including its developmental toxicity such as its effect on hatching, growth and survival, as well as its potential organ-specific toxicities such as cardiotoxicity, hepatotoxicity, and locomotion and behavioral toxicity, using zebrafish models. The results revealed that CB[7] has measureable cardiotoxicity and locomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
262
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(271 citation statements)
references
References 59 publications
(141 reference statements)
7
262
0
2
Order By: Relevance
“…8−10 For over a decade, we have been actively investigating the host−guest chemistry 11−17 and biocompatibility 18 of CB [7]. Recently, CB[n] (especially CB [7]) and derivatives have been demonstrated to reverse or inhibit the biological activities of a group of guest molecules due to strong host−guest complexations.…”
mentioning
confidence: 99%
“…8−10 For over a decade, we have been actively investigating the host−guest chemistry 11−17 and biocompatibility 18 of CB [7]. Recently, CB[n] (especially CB [7]) and derivatives have been demonstrated to reverse or inhibit the biological activities of a group of guest molecules due to strong host−guest complexations.…”
mentioning
confidence: 99%
“…On the one hand, CB [7]'s safety profile and biocompatibility has been well studied with several in vitro, in vivo and ex vivo models [5][6][7]. For instance, several in vitro studies on cell cultures have shown that CB [7] exhibits very low toxicity at up to 1 mM concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The effects observed for an intravenous single dose i.v. injection with a mouse model demonstrated that CB [7] has a very low acute toxicity at a dose of 250 mg/kg, based on a body weight change of less than 10% within 5 days of the injections [5]. The tissue specific toxicity including neuro-, myo-and cardiotoxicity of CB [7] has been examined with the use of ex vivo electrophysiological models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations